Assessment of Mandibular Distraction Regenerate Using Ultrasonography and Cone Beam Computed Tomography: A Clinical Study. Issue 1 (March 2016) - Dabas, Jitender; Mohanty, Sujata; Chaudhary, Zainab; Rani, Amita
Distraction osteogenesis (DO) is becoming a popular method of reconstruction for maxillofacial bony deformities or defects secondary to trauma or surgical tumor ablation. However, the technique is very sensitive in terms of the rate and rhythm of distraction. Because of this, there is a need for monitoring of the distraction regenerate during the distraction as well as the consolidation period. The present study was conducted to assess the regenerate using two imaging modalities, namely, ultrasonography (USG) and cone beam computed tomography (CBCT) to determine their relative efficacies and to weigh their clinical usefulness in assessment of DO regenerate. The study was conducted on 12 patients (18 sites) who underwent mandibular distraction for correction of facial deformities. The results showed that overall USG correlated better with the condition of regenerate ( r = 0.606) as compared with CBCT ( r = 0.476). However, USG was less effective as compared with CBCT in assessing the regenerate once corticomedullary differentiation occurred in the bone.